HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG ANEMIA DALAM KEHAMILAN TERHADAP KEPATUHAN KONSUMSI SUPLEMEN TABLET BESI DI PUSKESMAS PENEBEL I TAHUN 2022 - MONNA FRISCA WIDIASTIINI, PUTU; AYU PURNAMI, LUH; TRIGUNO, YOPITA (PRIMA WIYATA HEALTH, 2023)
Anemia is a widespread health problem in both developing and developed countries that is associated with an increased risk of morbidity and mortality, especially in pregnant women. According to the World Health Organization (WHO) 40% of maternal deaths in developing countries are related to anemia in pregnancy and most are caused by iron deficiency (Fe) and acute bleeding, and it is not uncommon for the two to interact with each other. Objective: To determine the correlation between knowledge level of pregnant women about anemia in pregnancy and behavior of consuming iron tablets in Penebel 1 Public Health Center in 2022. Methods: This research was an observational analytic survey with a cross sectional study approach. The number of samples in this study were 51 people with inclusion and exclusion criteria that had been determined by the researcher. Results: The results showed the results of the analysis p = 0.000 (p <0.05). Conclusion: that there is a relationship between Knowledge about Anemia and Compliance with Taking Iron Tablets at Penebel 1 Health Center.